The Impact of Artificial Intelligence (AI) Implementation on Islamic Financial Literacy and Global Economic Changes in the Banking World - KMT Lasmiatun; Nikzad Manteghi (IAIN Syekh Nurjati Cirebon, 2025)
Currently, the banking sector is facing a transformation towards the digital era in response to the development of fintech and the digital technology revolution. This transformation has brought banks into the era of digital banking services that aim to spread financial inclusion and provide access to the community without time and place constraints. Advances in information and communication technology have brought changes to various industries, including the Islamic finance sector. The development of artificial intelligence (AI) is crucial in the digitalization of Islamic money and offers opportunities to increase efficiency, personalize services, and reduce risks. This study aims to analyze the impact of AI implementation on financial literacy and global economic changes in the banking world by emphasizing effectiveness, efficiency, and compliance with Sharia principles. The research method used is qualitative literature research. Data comes from various sources, including relevant research papers, journals, and books. The findings of this study indicate that the application of AI in Islamic finance can improve operational efficiency, make financial services more accessible, and enable data analysis in a way that facilitates the development of strategic plans. However, the most important thing is to ensure that AI development complies with Sharia principles, including identifying riba, gharar, and non-halal transactions. The findings of this study highlight the importance of clear regulations to support the use of AI in Islamic finance, even if it is based on Islamic law. Through careful and innovative thinking, AI can serve as a strategic tool to enhance the Islamic banking sector in Indonesia, promote financial inclusion, and foster the country's economic growth.